Rasch analysis of student attributes: development and validation of scale to measure religious moderation - Zufriani Zufriani; Pitriani Pitriani; Albertos Damni (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
In Indonesia, the narrative of Religious Moderation is being hotly discussed and has even been included in the RPJMN 2020-2024. The target index has been determined, but measurement instruments are still minimal and can be used to measure the level of religious moderation at the university level. This research was conducted in response to these needs. The development of this instrument uses a unidimensional construct using Rasch analysis. The number of samples used was 406 students selected using the multistage random sampling technique. This development goes through three stages, namely item generation,where the objectives and concepts of measuring religious moderation are arranged to produce latent items. The theoretical analysisaims to test the scale's content validity.The last stage is a psychometric analysiswhich seeks to analyze the availability of the sample and construct the validity and reliability of the scale using Rasch analysis. The first stage produced 48 statements; thesecond stage resulted in changes in the religious context and usedmore appropriate words to describe the scale interval. The last stage makes 24 valid argumentsto be sureof religious moderation.